Topoisomerase inhibitors promote cancer cell motility via ROS-mediated activation of JAK2-STAT1-CXCL1 pathway - Liu, Jiafei (J Exp Clin Cancer Res, 2019)
BACKGROUND: Topoisomerase inhibitors (TI) can inhibit cell proliferation by preventing DNA replication, stimulating DNA damage and inducing cell cycle arrest. Although these agents have been commonly used in the chemotherapy for the anti-proliferative effect, their impacts on the metastasis of cancer cells remain obscure. METHODS: We used the transwell chamber assay to test effects of Topoisomerase inhibitors Etoposide (VP-16), Adriamycin (ADM) and Irinotecan (CPT-11) on the migration and invasion of cancer cells. Conditioned medium (CM) from TI-treated cells was subjected to Mass spectrometry screening. Gene silencing, neutralizing antibody, and specific chemical inhibitors were used to validate the roles of signaling molecules. RESULTS: Our studies disclosed that TI could promote the migration and invasion of a subset of cancer cells, which were dependent on chemokine (C-X-C motif) ligand 1 (CXCL1). Further studies disclosed that TI enhanced phosphorylation of Janus kinase 2 (JAK2) and Signal transducers and activators of transcription 1 (STAT1). Silencing or chemical inhibition of JAK2 or STAT1 abrogated TI-induced CXCL1 expression and cell motility. Moreover, TI increased cellular levels of reactive oxygen species (ROS) and promoted oxidation of Protein Tyrosine Phosphatase 1B (PTP1B), while reduced glutathione (GSH) reversed TI-induced JAK2-STAT1 activation, CXCL1 expression, and cell motility. CONCLUSIONS: Our study demonstrates that TI can promote the expression and secretion of CXCL1 by elevating ROS, inactivating PTP1B, and activating JAK2-STAT1 signaling pathway, thereby promoting the motility of cancer cells. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13046-019-1353-2) contains supplementary material, which is available to authorized users.